IbM Teacher of Early Childhood Education in Mempawah Hilir Sub District for Learning Tools Designing Based on 2013 Curriculum - Rody Putra Sartika; Lukmanul Hakim; Lukman Hadi (Universitas Tanjungpura, 2019)
The main goal of this IbM was to improve (1) knowledge and skills of the teacher from Malikian to design APE (2) knowledge and skills of the teacher from Tanjung and MAlikian to design K-13 based RKH, (3) knowledge and skills of the teacher from MAlikian and Tanjung on designing K-13 based evaluation instrument. The output of this IbM was (1) 8 APE, (2) 16 RKH, (3) 16 evaluation instrument. Methods of this activity were (1) giving a course to teachers how to design APE, RKH, and K-13 based evaluation instrument, (2) training teachers how to design APE, RKH, and instrument evaluation. (3) giving guidance of implementation of APE, RKH and K-13 based instrument evaluation. Evaluation of this activity was done two times which was done after the course and training activities. As a result, this IbM was successfully done without mistakes and obstacles.